2022
DOI: 10.3389/fonc.2022.816923
|View full text |Cite
|
Sign up to set email alerts
|

The COMT Genetic Factor Regulates Chemotherapy-Related Prospective Memory Impairment in Survivors With HER2−/+ Breast Cancer

Abstract: BackgroundPrevious findings indicated that polymorphism in gene catechol-O-methyltransferase (COMT) had been linked to chemotherapy-related cognitive impairment (CRCI). Nevertheless, the motivation of COMT polymorphisms in regulating cognitive impairment in breast cancer survivors with disparate status of human epidermal growth factor receptor 2 (HER2) was still vague.ObjectiveThe current research aimed to evaluate the regulation of the risk by COMT genotype on CRCI in breast cancer survivors with disparate st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…Other factors have been proposed to contribute to cognitive problems after surgery but before systemic therapy, including effects of general anesthesia [37,38], genotype [39], and differential in ammatory effects related to extent of resection [40]. This latter effect has been particularly pronounced in pre-clinical models with aged animals [41].…”
Section: Discussionmentioning
confidence: 99%
“…Other factors have been proposed to contribute to cognitive problems after surgery but before systemic therapy, including effects of general anesthesia [37,38], genotype [39], and differential in ammatory effects related to extent of resection [40]. This latter effect has been particularly pronounced in pre-clinical models with aged animals [41].…”
Section: Discussionmentioning
confidence: 99%
“…DNA damage of the central nervous system induced by chemotherapy is one of the essential mechanisms of CRCI in BC ( 40 ). The gene polymorphism of apolipoprotein E (ApoE), catechol-O-methyl-transferase (COMT), and BDNF was associated with CRCI ( 16 , 30 , 41 ). FMRI study found that the PM impairment in patients with BC was related to the abnormality of the brain network in the hippocampus and poor connection with prefrontal brain function after chemotherapy ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…This led to the conclusion that this allele, the APOE e2 genotype, provided a protective bene t on cognition (β = 0.32, 95% CI = 0.00 to 0.65). 13 Carroll 15 Overall, the ndings from the included studies suggest that increased leukocyte circulation, the DNMT1 rs2162560 A allele, 11 ER-/PR-genotype, HERgenotype, and increased DNA methylation-especially at the CpG regions-leads to increased complaints of CICI in BCPs and survivors. 12 Furthermore, having the APOE e2 genotype serves as a protective factor against CICI.…”
Section: Geneticsmentioning
confidence: 96%
“…[11][12][13] For example, Yao et al and Chan et al observed the protective effect of DNA methylation 12. Van Dyke et al andLi et al correlate APOE to CICI, but differ in their ndings 13,15. Li et al additionally explores COMT polymorphisms with regards to increased CICI risk 15.…”
mentioning
confidence: 99%